Analysis and Implementation of the Policy on the Nine Steps of West Java Education Development Toward the Realization of the “Gapura Panca Waluya” - Nurleli, Leli; Febrianti, Tinah; Gaffar, Muhammad Andriana; Wasliman, Eva Dianawati; Nugroho, Iwan Satriyo (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2026)
Character education faces unprecedented challenges in Indonesia's disruptive era, where digitalization and socio-cultural shifts threaten the internalization of values ??among the younger generation. West Java Province responded to this with the transformative Gapura Panca Waluya framework—articulated through nine policy steps in Governor's Circular Letter No. 45/PK.03.03/KESRA—to cultivate students who embody cageur (holistic health), bageur (moral excellence), bener (honesty), pinter (intellectual competence), and singer (adaptive agility). Despite its philosophical sophistication, critical gaps remain between policy design and implementation at the school level. This study analyzes the alignment between the Nine Steps policy and its operationalization in elementary schools, identifies contextual factors that influence implementation fidelity, and proposes an adaptive model for character education in the digital age. Using a qualitative descriptive approach with a policy analysis design, this study integrates analysis of national and provincial regulatory documents, 84 hours of non-participant observation in six purposively selected schools in Bekasi Regency, and semi-structured interviews with 24 stakeholders (principals, teachers, parents).